Sistem Informasi Sepeda Motor Dengan Metode User Centered Design - Ginting, Gusto Gibeon; Anom Cahyadi Putra, I Gusti Ngurah; Raharja, Made Agung; Sanjaya ER, Ngurah Agus; Gede Suhartana, I Ketut; Mastrika Giri, Gst. Ayu Vida (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 2 (2023): JELIKU Volume 12 No 2, November 2023, 2023)
Today, vehicles are a major need for humans, especially motorcycles. In Indonesia alone the number of motorcycle population is more than other types of vehicles. The use of motorbikes is considered more effective because of low operational costs, economical fuel consumption and more environmentally friendly, and a wider range of mobility due to their not too large size and easy use. Because of this, various brands of industrial companies are circulating in the market, so that it is difficult for people to choose a motorbike. To realize this, a research entitled Motorcycle Information System Using the User Centered Design Method was carried out. In this study, the researcher will later add a recommendation feature to the built website, this feature will later compare in terms of a smaller value than the variable inputted by the user, to run this feature, the researcher adds a selection sort algorithm as an algorithm for comparing values between variables. This study aims to design a website-based user interface and user experience. Where it is, proportional to the increase in the number of purchases of existing motorcycles. The website that has been made was tested on the General Public and Informatics Students with a total of 20 respondents. To find out the level of satisfaction of respondents in using the motorcycle recommendation website, usability testing was carried out using the system usability scale method. This method measures the usability of a computer system according to the user's subjective point of view by filling out a Likert-scale questionnaire. The website that has been made is tested on the General Public and Informatics Students. To find out the level of satisfaction of respondents in using the motorcycle recommendation website, usability testing was carried out using the system usability scale method. This method measures the usability of a computer system according to the user's subjective point of view by filling out a Likert-scale questionnaire.